2020
DOI: 10.3390/biom10050794
|View full text |Cite
|
Sign up to set email alerts
|

Crotoxin-Induced Mice Lung Impairment: Role of Nicotinic Acetylcholine Receptors and COX-Derived Prostanoids

Abstract: Respiratory compromise in Crotalus durissus terrificus (C.d.t.) snakebite is an important pathological condition. Considering that crotoxin (CTX), a phospholipase A2 from C.d.t. venom, is the main component of the venom, the present work investigated the toxin effects on respiratory failure. Lung mechanics, morphology and soluble markers were evaluated from Swiss male mice, and mechanism determined using drugs/inhibitors of eicosanoids biosynthesis pathway and autonomic nervous system. Acute respiratory failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 86 publications
(101 reference statements)
0
10
0
4
Order By: Relevance
“…The widespread presence of the neurotoxic phospholipase A 2 crotoxin in several species ( 33 37 ) places most Neotropical rattlesnakes (at least in early life stages) in the Type II venom category described by Mackessy ( 38 ). This class includes species possessing highly toxic venoms characterized by systemic neurotoxicity inducing rapid paralysis due to respiratory failure, rather than hemorrhagic symptoms ( 39 42 ). Conversely, phenotypes that are dominated by hemorrhagic and tissue-destroying snake venom metalloproteases (SVMPs) and generally devoid of neurotoxins are classified into the Type I category ( 38 ), which encompasses low-toxicity venoms inducing mostly cytotoxic and/or hemotoxic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread presence of the neurotoxic phospholipase A 2 crotoxin in several species ( 33 37 ) places most Neotropical rattlesnakes (at least in early life stages) in the Type II venom category described by Mackessy ( 38 ). This class includes species possessing highly toxic venoms characterized by systemic neurotoxicity inducing rapid paralysis due to respiratory failure, rather than hemorrhagic symptoms ( 39 42 ). Conversely, phenotypes that are dominated by hemorrhagic and tissue-destroying snake venom metalloproteases (SVMPs) and generally devoid of neurotoxins are classified into the Type I category ( 38 ), which encompasses low-toxicity venoms inducing mostly cytotoxic and/or hemotoxic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Local manifestations are commonly associated with the inflammatory properties that venom can trigger once inoculated. Although toxins from C. durissus subspecies are known to present low immunogenicity, studies have shown the capacity of venoms and toxins to promote local and systemic inflammatory responses in animal models ( 78 , 121 , 122 ). As previously described, C.d.…”
Section: Human Envenomations Caused By C D Ruruimamentioning
confidence: 99%
“…ruruima “yellow” and “white” venom variations are responsible for inducing mouse paw edema ( 112 ). Considering that the venom components crotoxin and serine proteases are found to trigger an inflammatory response ( 78 , 122 ), the higher frequency in local manifestations, such as edema, found in Roraima state could be associated with C. d. ruruima venom composition, in which the two toxins classes comprise over 90%. Moreover, although the low abundance of SVMP found in C. d. ruruima venom can be associated with rare cases of local sequelae, this group of toxins could be an additional factor for local injury as observed for North American Crotalus spp.…”
Section: Human Envenomations Caused By C D Ruruimamentioning
confidence: 99%
“…ruruima -yellow‖ and -white‖ venom variations are responsible for inducing mouse paw edema [112]. Considering that the venom components crotoxin and serine proteases are found to trigger an inflammatory response [78,122], the higher frequency in local manifestations, such as edema, found in Roraima state could be associated with C. d. ruruima venom composition, in which the two toxins classes comprise over 90%. Moreover, although the low abundance of SVMP found in C. d. ruruima venom can be associated with rare cases of local sequelae, this group of toxins could be an additional factor for local injury as observed for North American Crotalus spp.…”
Section: Local Complications Such As Secondary Infections and Compartment Syndrome Seem To Appear At Very Low Frequency Inmentioning
confidence: 99%